Analysis of the Repetition and its Impact on the Completion of the Program of Studies in the 2014 Cohort of the School of Engineering and Industrial Sciences - Rivera-Gaibor, Juan Carlos (2020)
The purpose of the article is to determine the time it takes a student to pass the curriculum, incorporating repetition as the factor that influences the percentage of progress at each level. The analyzed population is new students from the 2014 cohort of the seven face-to-face courses at the Quito campus of the Faculty of Engineering Sciences and Industries, for the periods March 2014 - July 2014 (n = 417), September 2014 - February 2015 (n = 353). The methodology is a documentary case study, based on the inductive-deductive, analytical and synthesis method using the excel electronic sheet. As results, it can be determined that the students who have not completed their study plan at the nine levels, will require at most three additional periods. One cause of dropout is the high level of repetition in the lower levels of each of the races, so it is necessary to carry out studies that explain the causes of these results. For the period March 2014 - July 2014, 15.68 % and for September 2014 - February 2015, 25.26 % of the students pass the study plan at the nine levels.